Threshold Reaction of Soil Arthropods to Simulative Nitrogen Deposition in Urban Green Spaces - Mo, Lingzi; Xu, Guoliang; Zhang, Jiaen; Wu, Zhifeng; Yu, Shiqin; Chen, Xiaohua; Peng, Bin; Squartini, Andrea; Zanella, Augusto (Frontiers in Ecology and Evolution, 2021)
Sustained nitrogen (N) deposition has a wide-ranging impact on terrestrial ecosystems. However, still little attention has been paid to responses of urban soil fauna to the increasing N deposition. To clarify such effects on the soil properties and soil fauna in typical urban lawns (featuring Cynodon dactylon vegetation), a control experiment was conducted for 1 year, in which NH4NO3 was added as the external N source with four treatments of N addition: N0 (i.e., only water), N1 (50 kg N ha–1 yr–1), N2 (100 kg N ha–1 yr–1), N3 (150 kg N ha–1 yr–1). Results showed that N additions influence soil faunal communities in the urban lawns soil. The relative abundance of Oribatida increased with the N treatment level, partially replacing the more sensitive Collembola. Significant differences in the Shannon-Wiener and Margalef indices (p < 0.01) supported this statement. Although higher doses of N addition showed adverse effects on soil fauna communities, low N inputs increased the soil fauna diversity and richness, especially at 5–10 cm depth. A threshold effect appears to exist: low N addition (<25 kg N ha–1) did not negatively affect pedofauna structure and composition, while in the range from these values up to 50 kg N ha–1, the composition of the soil fauna underwent major changes which were confirmed by the decline of biodiversity indices. These changes are accompanied by the decreased pH values with increasing N inputs.